PERAN E-WOM, LIFE STYLE, KEPERCAYAAN, DAN CONTENT MARKETING DALAM KEPUTUSAN PEMBELIAN GENERASI MILENIAL DI FACEBOOK - Muhammad Ferdianto; Rahmat Solling Hamid; Edi Maszudi (FEB Universitas Sam Ratulangi Manado, 2023)
This study aims to examine the effect of e-wom, life style, trust, and content marketing on purchasing decisions. The total number of the population in this study is unknown, so the sample was taken using a non-probability sample and a total of 150 respondents were obtained. Hypothesis testing using the Structural Equation Model technique. Based on the research results, e-wom has a direct significant effect on purchasing decisions, life style has a direct significant effect on purchasing decisions, trust has a direct significant effect on purchasing decisions, and content marketing has a direct significant effect on purchasing decisions. Keywords: e-wom, life style, trust, content marketing and purchasing decisions.